Restricted dynamic observer error linearizability. (March 2015) - Lee, Hong-Gi; Kim, Kyung-Duk; Jeon, Hong-Tae
Abstract: Following the general dynamic observer error linearization problem, state equivalence to a triangular nonlinear observer canonical form with index d and the restricted dynamic observer error linearization problem are defined. In this paper, the necessary and sufficient conditions for the above two problems are given. Since our proofs are constructive, a desired state transformation can also be found in the theorem.